Chronic myeloid leukemia: diagnosis and treatment - Hehlmann, Rüdiger (Springer, 2016)
This book provides state-of-the-art reviews of key issues and recent developments relating to chronic myeloid leukemia (CML), acquainting the reader with advances in research, treatment, and promotion of public health. Among the management topics addressed are the choices, advantages, and pitfalls of first-, second-, and third-line treatments; the European LeukemiaNet recommendations; management of adverse effects of tyrosine kinase inhibitors (TKI); management of CML blast crisis; management of pregnancy in the context of CML; the role of hematopoietic cell transplantation; the current experience with TKI discontinuation; and the value of interferon α in improving the outcome of TKI treatment. Various aspects of relevance to treatment outcome are discussed, including prognostic scores, molecular monitoring (principles and interlaboratory standardization), and response-related predictors of survival. Furthermore, updates are provided on the increasing prevalence of CML and its implications and on the changing cost of care for CML, taking into account the forthcoming impact of availability of generic imatinib
Keywords: Myelose; Chronisch-myeloische Leukämie